Climate change-mediated heat stress vulnerability and adaptation strategies among outdoor workers. (9th August 2022) - Odonkor, Stephen T.; Adams, Samuel
ABSTRACT: The study examined the effect of heat stress on the well-being of outdoor workers and their coping strategies. A cross-sectional survey study was conducted between September 2019 and December 2019 to collect data from outdoor workers including hawkers and traffic wardens from 13 urban areas ( N  = 322) and analyzed using SPSS v.23. The results of the study show that most of the outdoor workers were in a good health state based on their self-health assessment. However, the respondents expressed concerns and symptoms of heat stress including heat cramps, heat exhaustion, heat stroke and sleep disorders. The findings also show that male outdoor workers were 1.3 times more likely than females to be affected by heat stress. Respondents in their 20s were more likely to be affected by heat stress, as a result of temperatures and humidity conditions, than those in their 30s (OR = 0.389, CI = 0.158–0962) and 40s (OR = 0.395, CI = 0.147–1.063). Coping strategies identified include the use of breathable cotton attires, drinking a lot of water, hiding under shades and reducing outdoor activity intermittently.